Pengaruh Co-Creative Tourism Experience terhadap Revisit Intention Pada Kuliner Karawang - Faishal Burhanudin, Mochamad; Yusuf, Abdul (www.bsi.ac.id, 2023)
The purpose of this study is to ascertain the degree to which the co-creative tourist experience (X) affects on revisit intention (Y) in the Karawang culinary. The research uses a descriptive quantitative methodology and obtained samples from The 70 participants in the Karawang culinary tasters research served as the samples for the data processing, which was done using the SPSS program. Both primary and secondary data were collected by questionnaire distribution and literature reviews, respectively. employing correlation and regression analysis to analyze data. The result showed that The co-creative tourism experience variable partially influences the revisit intention variable favorably. The reliability score is 0.93, while the validity score is 0.235. The findings revealed that co-creative tourist experience had a 71.8% effect on revisit intention and a 28.2% influence on co-creative tourism experience. In other words, the study demonstrates that the co-creative tourism experience can positively affect the intention to return for culinary tourism in Karawang Regency. In order to enhance their offers and draw back customers, tourist places may benefit greatly from the information provided by this study.